A Brief Review on Nano-Catalysis and Its Applications: Exploring the Potential of Nano-Catalysis for Enhanced Energy Conversion (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the time of nanoscience, when all gadgets and developments are decreasing and littler with improved properties catalysis is a significant area of research. With this in mind, we present a summary of the applications of nanoscience in catalysis, energy conversion, and energy conservation. In the present study we are trying to condense in-writing knowledge that is beneficial to individuals to use nano-estimated inspiration in day-to-day life. Improvement of synergistic properties is discussed here due to reduced impetus size to nano scale.